Enhanced Nonlinearity and Engineered Anomalous Dispersion in TeO2-coated Si3N4 Waveguides - Hamidu M. Mbonde; Henry C. Frankis; Jonathan D. B. Bradley (IEEE Photonics Journal)
We propose designs of silicon nitride (Si3N4) waveguides with enhanced nonlinear parameter and engineered anomalous group velocity dispersion (GVD) by addition of tellurium oxide (TeO2) top-coating layers of various thicknesses. The proposed waveguides have calculated nonlinear parameters of up to three times that of stoichiometric Si3N4 and exhibit anomalous GVD at near infrared wavelengths. The GVD of such waveguides can be tuned between the normal and anomalous regime with different zero dispersion wavelengths by adjusting the thickness of TeO2 coating. These designs offer promise of higher performance nonlinear devices on a standard low-loss Si3N4 platform with the possibility of integration of active functionalities owing to higher solubility of rare earth dopants in tellurium oxide.